Kelas Prenatal Yoga terhadap Kualitas Tidur Ibu Hamil - Saputri, Sindika Aprilia; Sulastri, Sulastri (Journal of Telenursing (JOTING), 2023)
This study aims to determine how prenatal yoga classes influence the sleep quality of pregnant women at PMB Wulan Mardikaningtyas. The quantitative research method uses a quasi-experimental method with a Pretest-Posttest Control Design. The data research results showed that after carrying out prenatal yoga, the average score for sleep quality decreased, namely from 9.47 to 4.03. The results of statistical tests using the paired sample t-test show that the p-value = 0.000, where the p-value <0.05. In conclusion, there is an influence of prenatal yoga classes on the sleep quality of pregnant women at PMB Wulan Mardikaningtyas. Keywords: Pregnant Women, Sleep Quality, Prenatal Yoga